2007
DOI: 10.1262/jrd.18108
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Granulin in Estrogen-Induced Neurogenesis in the Adult Rat Hippocampus

Abstract: Abstract. Recent studies have demonstrated the presence of neurogenesis in the adult mammalian hippocampus, and it has been suggested that estrogen and various growth factors influence the processes of adult neurogenesis. The present study assessed cell proliferation in the dentate gyrus and the mRNA expression levels of granulin, insulin-like growth factor-I (IGF-I), and brain-derived neurotrophic factor (BDNF) in the hippocampus 4 h after treatment with estradiol benzoate (EB) in 3-and 12-month old ovariecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…Further studies using neural and glial markers would be needed to examine the reason for this discrepancy. PGRN expressed in the hippocampus, especially in the dentate gyrus, is proposed to play roles in facilitating the estrogen-induced adult neurogenesis that takes place in this brain region [10]. The amygdala participates in inducing emotional reactions [19], and the PGRN-deficient mice showed an enhanced level of aggression and anxiety in our previous study [11].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Further studies using neural and glial markers would be needed to examine the reason for this discrepancy. PGRN expressed in the hippocampus, especially in the dentate gyrus, is proposed to play roles in facilitating the estrogen-induced adult neurogenesis that takes place in this brain region [10]. The amygdala participates in inducing emotional reactions [19], and the PGRN-deficient mice showed an enhanced level of aggression and anxiety in our previous study [11].…”
Section: Discussionmentioning
confidence: 74%
“…Since the PGRN gene is a sex steroid-inducible gene, this age-dependent decrease in PGRN gene expression may be at least partially due to a decrease in the sex steroid levels in the peripheral circulation with age. On the other hand, we have previously shown that estrogen increases PGRN gene expression as well as neurogenesis in the hippocampus of 3-month-old rats, but the effects of estrogen on both gene expression and neurogenesis are no longer discernible in 12-month-old rats [10]. It is therefore suggested that the responsiveness to sex steroids in PGRN gene expression also declines with age.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…New neurons are produced from these progenitors in response to the mitogenic signals of EGF, TGF, VEGF and NPY (Craig et al, 1996;Kuhn et al, 1997;Tropepe et al, 1997;Schanzer et al, 2004;Howell et al, 2005;Chiba et al, 2007). The majority of these progenitor cells typically express Pax6 during proliferation with expression down-regulated upon exit from the cell cycle and entry into a migratory phase (Kohwi et al, 2005;Maekawa et al, 2005).…”
Section: Pax Expression In Progenitor Cells Of Adult Tissuementioning
confidence: 99%
“…Our previous studies have demonstrated that it mediates the organizing effects of sexsteroid hormones in the process of sexual differentiation of the brain [9][10][11][12][13]. PGRN also mediates estrogen-induced adult neurogenesis [14]. Mutations including the null mutation in the PGRN gene have been found in patients with frontotemporal dementia with ubiquitin-immunoreactive neuronal inclusions [15,16].…”
mentioning
confidence: 99%